Optimasi Formulasi Pasta Ubi Jalar Ungu dan Tepung Terigu terhadap Daya Kembang dan Mutu Hedonik Roti Tawar - Apriliyanti, Mulia W; Kurnianto, Mokh. F; Suryaningsih, Wahyu; Saleh, Anang S (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Bread is a fermented product that undergoes several processing stages, including the mixing of wheat flour, water, yeast, and salt, followed by kneading, fermentation, shaping, and baking. Wheat flour is essential in bread making because its gluten content influences the bread’s expansion and texture. In this research, part of the wheat flour was replaced with purple sweet potato paste to reduce reliance on wheat flour. Ipomoea batatas cultivar Ayamurasaki or purple sweet potato, has potential as a functional food due to its rich nutritional profile and naturally vibrant purple color. This study employed a D-Optimal Mixture Design using the optimal custom design expert model, consisting of two factors: purple sweet potato paste 10–60% and wheat flour 40–90%, evaluated across five response variables: expansion power, hedonic quality of crumb color, crumb texture, pore structure, and taste. The analysis was performed using Design-Expert 13 software, involving a total of eight formulations. The optimization results predicted that the formulation containing 60% purple sweet potato paste and 40% wheat flour produced the most optimal white bread, with expansion power of 46.56%, a hedonic score for crumb color of 5.30 (deep purple, a crumb texture score of 5.06 (soft, a pore structure score of 3.58 (moderately uniform, and a taste hedonic score of 5.30 (distinct purple sweet potato flavor, yielding a desirability value of 0.95.